EFFECT OF METHOD CIRCUIT TRAINING AEROBIC FOR ENHANCEMENT POWER ENDURANCE LEG MUSCLE - Hamdani, Odin (Journal Physical Education, Health and Recreation, 2019)
Sports achievement is a sport that fosters and develops sportsmen in a planned, tiered, and supported through competition to achieve achievements with the support of sports science and technology. The problem that occurs is the calendar of the competition that is not on time. The purpose of the study was to find out how to increase power endurance of leg muscle after being given an aerobic circuit training program. The research method was use The One-Group Pretest-Posttest Design by giving treatment to ten FPOK UPI Sports Science first-level students. The result show that circuit training aerobic has a significant impact on increasing power endurance of leg muscle, the pre-test received an average of 39.00 then after being given treatment with circuit training aerobic, the average post-test results were 54.20. Hypothesis test results show a significance value of 0,000 <0,05, then H0 is rejected. It can be concluded that there is an effect of aerobic circuit training on increasing the power endurance ability of the leg muscles.